Kajian Kimia dalam Sistem Kehidupan Melalui Pendekatan Kontekstual Berbasis Kearifan Lokal Dalam Pembelajaran Kimia: Tinjauan Literatur - Nur Azizah Dj. Junus; Astin Lukum; Masrid Pikoli (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
The study of chemistry in living systems through a contextual approach based on local wisdom aims to (1) identify publication trends; (2) identify dominant research subjects; (3) examine learning approaches; (4) identify chemical materials most frequently associated with living systems; (5) describe forms of local wisdom integration; and (6) examine the research methods used. This study uses the Systematic Literature Review (SLR) method with a qualitative descriptive design for articles from the 2020–2026 period. The research procedure includes identification, selection, analysis, and synthesis of articles based on inclusion and exclusion criteria. The research objects are scientific articles on local wisdom-based chemistry learning. Data were collected through scientific database searches and analyzed descriptively. Of the 50 articles found, 17 articles met the analysis criteria. The results of the study show that: (1) publications increased in 2023–2025; (2) research subjects were dominated by high school students; (3) the ethnochemical approach was most widely used; (4) frequently studied materials included acids and bases, environmental chemistry, and colloidal systems; (5) integration of local wisdom is carried out through cultural analogies, utilization of local resources, and the environment as a learning context; and (6) type of research dominated by qualitative and development approaches. In conclusion, local wisdom-based chemistry learning has the potential to strengthen the relevance of learning and students' chemical literacy.